The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1021/ja035026f
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic Evidence for Hydrogen Diffusion through a Several-Nanometers-Thick Titanium Carbonitride Layer on Silicon

Abstract: Multiple internal reflection Fourier transform infrared spectroscopy, together with other analytical techniques, was used to follow the diffusion of atomic hydrogen through a 10-nm-thick titanium carbonitride layer deposited onto a Si(100)-2x1 surface from tetrakis(dimethylamino)titanium as a chemical vapor deposition precursor. The recombinative desorption of hydrogen from the TiCN/Si interface was shown to coincide with the temperature range where most Ti-based diffusion barriers break down.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…The work by Qin et al 75 and Zeng et al 76 demonstrates penetration of hydrogen atoms through such an amorphous, thermally deposited layer of Ti/TiO 2 several tens of nanometers thick deposited on a Pd electrode in an electrochemical cell. Penetration of thin films has also been demonstrated for 10 nm thickness Ti carbonitride 77 and using atomic and plasma hydrogen sources. 78 Thus, we consider it highly plausible for the atomic hydrogen to penetrate the metal electrode covering the nanowire and affect the underlying oxide at the metal−nanowire junction.…”
Section: Nano Lettersmentioning
confidence: 96%
“…The work by Qin et al 75 and Zeng et al 76 demonstrates penetration of hydrogen atoms through such an amorphous, thermally deposited layer of Ti/TiO 2 several tens of nanometers thick deposited on a Pd electrode in an electrochemical cell. Penetration of thin films has also been demonstrated for 10 nm thickness Ti carbonitride 77 and using atomic and plasma hydrogen sources. 78 Thus, we consider it highly plausible for the atomic hydrogen to penetrate the metal electrode covering the nanowire and affect the underlying oxide at the metal−nanowire junction.…”
Section: Nano Lettersmentioning
confidence: 96%
“…3.40, it was concluded that the remaining species is the hfac ligand bonded to a copper atom, which is in turn bound to silicon surface, structure A [356]. These findings were later expanded to explain the structural characteristics of thin diffusion barrier film, TiCN [360][361][362], and to understand the chemical reactivity of its surface [363,364] with respect to the copper deposition process. Most of the other investigations of the effects of a metal presence on the chemistry of organometallic molecules are related to the chemistry of deposition of metals and metal compounds onto silicon.…”
Section: Effect Of Metal Atoms On the Pathways Of Chemical Reactions mentioning
confidence: 99%
“…The characteristics and properties of the film created following this procedure have been documented previously. 3 The alkenes, deuterated ethylene, C 2 D 4 (Sigma-Aldrich, 99%), and vinyltrimethylsilane, VTMS (Aldrich, 99%), were adsorbed on the deposited TiCN film at 300 K. Isotopically substituted ethylene was used instead of C 2 H 4 because its cracking pattern is very easy to follow with a mass spectrometer, as it is mostly unaffected by the presence of any background gases in the UHV chamber. Saturation doses were previously found to be 1000 L for C 2 D 4 13,18 and 100 L for VTMS.…”
Section: Experimental and Computational Methodsmentioning
confidence: 99%
“…However, these films are often contaminated by carbon, especially when metal–organic compounds are used as deposition precursors in chemical vapor deposition (CVD), leading to the films of a general formula MC x N y , where M is a transition metal. As we have shown previously, the TiCN film can be grown from the tetrakis-(dimethylamino)-titanium (TDMAT) metal–organic precursor using CVD onto a clean surface of the Si(100)-2 × 1 single crystal and is composed of titanium, carbon, and nitrogen. The elemental composition corresponds to a 1:1:1 ratio of Ti to C to N, as was determined by X-ray photoelectron spectroscopy (XPS) and Auger electron spectroscopy (AES), and therefore the film can be best described as TiCN. ,, Transmission electron microscopy (TEM) has shown that this TiCN film is composed of crystallite nanostructures imbedded in an amorphous matrix. , Previous studies indicate that its surface chemistry is governed by localized surface reactive sites, , making computational cluster modeling of the surface properties of this film possible. It should be noted that carbides and nitrides of transition metals have been previously investigated with density functional theory (DFT) using cluster models with fixed positions of the atoms representing single crystalline surfaces .…”
Section: Introductionmentioning
confidence: 98%